Functional disorders of the respiratory system in patients with penetrating lung wounds: study prospective design - Olga I. Savushkina; Andrey A. Zaytsev; Maria M. Malashenko; Nataliya A. Aseeva; Pavel A. Astanin; Denis V. Davydov; Evgeniy V. Kryukov (ZAO "Consilium Medicum", 2022)
Background. Lung function tests should be performed to patients with penetrating wounds of the lungs to identify lung function disorders, and the data obtained should be taken into account when correcting medical treatment and prescribing individual medical rehabilitation programs. The aim was to study the impact of penetrating lung wounds on the lung function in the early recovery period. Materials and methods. 13 patients were enrolled in the study, 100% male, median age 26 [21; 31] years. Spirometry, body plethysmography, and a diffusion test were performed on an average of 14 days from the injury. Results. A prospective cross-sectional study was performed. A moderate decrease in the vital capacity (VC), the forced vital capacity (FVC), the volume of forced exhalation in the first second (FEV1) was revealed while the total lung capacity (TLCpl) and the FEV1/FVC ratio were within normal values. However, in 2 (15.4%) and 3 (23%) patients, a restrictive ventilation disorders (TLC lower limit of normal) was detected when using Global Lung Function Initiative (GLI) and European Community for Steel and Coal (ECSC) 1993 predicted value system, respectively. The residual lung (RV) and RV/TLCpl were increased. Functional residual capacity (FRC), FRCpl/TLCpl, airway resistance remained within normal values. The diffusion lung capacity impairment was detected in 92.3% and 61.5% cases according to the ECSC 1993 and the GLI system, respectively. Conclusion. In the early period of recovery after penetrating lung wounds, a nonspecific pattern of ventilation disorders was the most often abnormality namely a decrease in VC while TLC and FEV1/FVC were within normal values. Less frequently, the classic restrictive pattern of ventilation disorders was diagnosed. Besides, the diffusion lung capacity impairment was detected. The system of predicted values has a significant impact on the frequency of detection of the lung function disorders. The revealed functional disorders should be taken into account for adjusting medical and rehabilitation interventions.